Valorization of oil palm empty fruit bunches into activated carbon: A mini-review - Agus Pratama, Andhika Putra; Rohma, Novita Ainur; Elviliana, Elviliana; Nafi'ah, Riris Waladatun; Setyawan, Hendrix Yulis; Sabrina Sunyoto, Nimas Mayang; Fatriasari, Widya; Suhartini, Sri; Jung, Young Hoon; Idrus, Syazwani; Melville, Lynsey (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
This paper aimed to comprehensively review the potential valorization of oil palm empty fruit bunches (OPEFBs) into activated carbon and its potential application. Activated carbon is carbon processed through dual phases, including carbonization and activation. Firstly, this process converts biomass into carbon thermally with zero to little oxygen conditions. Next, the carbon needs to be activated to stimulate the formation of pores and reduce impurities. The activated carbon’s quality is influenced by the activation process, which can be done physically, chemically, or physiochemically. Activated carbon has an amorphous structure and abundant internal pore structure, thus increasing the surface area. In Indonesia, the quality of active carbon is regulated by Indonesian National Standards or SNI 06-370-1995.  The factors influencing the activation step include activator agent type,  activator agent concentration, activation ratio and time, etc. . Generally, activated carbon can be widely applied to various sectors, such as agriculture (i.e., slow-released fertilizer, fertilizer, etc.), waste treatment (i.e., adsorbent, activator in anaerobic digestion/AD, bioremediation, etc.), gas purification, ceramic membrane, etc. However, further in-depth investigation is required to determine potential scaling-up and commercialization.